The Prevalence of Polypharmacy and Potentially Inappropriate Medications and Its Relationship with Cognitive Status in Portuguese Institutionalized Older Adults: A Cross-Sectional Study - Caçador, Catarina (2022)
The aim of this study was to evaluate the prevalence of polypharmacy and potentially inappropriate medications (PIMs) in a population of older adults living in nursing homes. Furthermore, we also intended to assess the possible association between polypharmacy, potentially inappropriate medications and cognitive impairment in institutionalized older adults. A cross-sectional study analyzed data from 193 nursing home residents in the district of Viseu, Portugal, between September 2018 and June 2019, with a mean age of 82.4 ± 6.2 years (ranging from 65 to 95 years old); 72.5% (n = 140) were female participants. Major polypharmacy was presented in 80.8% of the study population, who took 7.6 ± 3.3 drugs per day. Using the Beers Criteria, we found that 79.3% took PIMs. There was a positive association between polypharmacy and PIM (p < 0.001), showing that higher medicines intake increased the number of PIMs. Polypharmacy was not associated with the functionality of the older adults to perform activities of daily living, but was associated with cognitive impairment. The older adults with lower scores on the Mini Mental State Examination (MMSE) took more drugs (p = 0.039) and used more PIM (p < 0.001). Moreover, patients taking five or more prescription drugs per day (major polypharmacy) consuming any psychiatric, gastrointestinal or oral antidiabetic agents (regardless of whether they were considered potentially inappropriate or not) had higher odds of displaying cognitive impairment than those who did not (p < 0.05). Older adult residents of the studied nursing homes were potentially affected by polypharmacy and inappropriate polypharmacy. This observation reveals the need to adopt and implement strategies that make drug therapy more adequate and safer for older adults.